Effects of cultivation and recovery on soil organic matter and N mineralization in shortgrass steppe - Ihori, Tamiko, author; Burke, Ingrid C., advisor; Binkley, Dan, committee member; Lauenroth, William K., committee member; Coffin, Debra P., committee member (Colorado State University. Libraries, 1993)
Understanding cultivation effects on soil organic matter (SOM) and available nutrients to plants is important, because SOM is an important storage of C globally and available nutrients are an important factor in plant growth. It is also important to understand recovery from disturbance such as cultivation. I conducted two studies: one on total SOM and the other on in situ N mineralization in native, cultivated, and recovering abandoned fields in the shortgrass steppe of northeastern Colorado. I examined total C and N content in 30 cm depth soil of native fields, abandoned fields that were historically cultivated and then abandoned about 50 years ago, and cultivated fields that were cultivated more than 50 years, at 13 sites in the Pawnee National Grasslands. Both total C and N were highest in native, intermediate in abandoned, and lowest in cultivated fields. An average loss from cultivation for total C was 26% and for total N was 29%. Precipitation had a significant effect on SOM content in native fields, but did not have an effect on C and N losses from cultivation. C/N ratio differences among native, abandoned, and cultivated fields were not significant in 30cm depth soil. I estimated recovery of SOM using the CENTURY model. During 50 years of abandonment of lands, I estimate that 25 g/m² of C has recovered, but we could not detect N recovery. In situ net mineralization in 15 cm depth soil was also examined among three land management treatments (native, abandoned, and cultivated) and two microsites (under individual Bouteloua gracilis plants and between individual plants). Total C, N, and C/N ratios were highest in native, intermediate in abandoned, and lowest in cultivated fields, and higher under plants than between plants. In situ net N mineralization, % N mineralization, and moisture content in soils were highest in cultivated fields, but there was no difference between native and abandoned fields. In situ net N mineralization, % N mineralized, and soil moisture content were not significantly different between microsites. A ratio of field net N mineralization to lab net mineralization was highest in cultivated fields, but differences between native and abandoned fields were not significant. This ratio tended to be higher between plants than under plants, but there was not a significant difference. Because this ratio may be an index of environmental limitation to N mineralization, I infer that cultivated fields and between plant locations have less environmental restriction than native fields or underplant locations. I concluded from these results that nitrogen availability to plants is recovered in abandoned fields from the results of in situ N mineralization. However total C has recovered only 25 g/m², and total N did not show recovery in abandoned fields.
Keywords: Steppes; Steppe soils